Altered red blood cell distribution width in overweight adolescents and its association with markers of inflammation. Issue 5 (13th December 2012) - Fujita, B.; Strodthoff, D.; Fritzenwanger, M.; Pfeil, A.; Ferrari, M.; Goebel, B.; Figulla, H. R.; Gerdes, N.; Jung, C.
Summary: What is already known about this subject: Red cell distribution width correlates with outcomes in numerous clinical populations. RDW is elevated in inflammatory states. Obesity is associated with inflammation. What this study adds: RDW is elevated in obese adolescents. RDW represents a potential marker for the presence of metabolic syndrome. Background: Obesity and the metabolic syndrome are dramatically increasing problems. Red blood cell distribution width (RDW), the variability in size of circulating red blood cells, has been demonstrated to be altered in different clinical settings. This analysis aimed to investigate the relationship between RDW and obesity in adolescents and in an animal model of diet‐induced obesity (DIO). Methods: Seventy‐nine male adolescents (aged 13–17 years) were studied. Thirty‐seven of them were overweight (body mass index ≥ 90th percentile). RDW, markers of inflammation and stem cell factor (SCF) were determined. In an animal study, mice were fed with different diets for 15 weeks. RDW was determined using an animal blood count machine. Results: RDW differed significantly between normal‐weight adolescents (13.07 ± 0.09) and overweight adolescents (13.39 ± 0.10, P = 0.015), whereas erythrocyte counts and haematocrit did not differ. RDW correlated to markers of inflammation and inversely to SCF. In the mice animal model, nutritional changes increased RDW, whereas overweight per se did not change RDW. Conclusions: RDW is elevated in overweight and reflects the inflammatory state. RDW potentially represents an additional and cost‐effective tool to indicate inflammation. Future studies are needed to understand the differential influences of nutrition and overweight on RDW.